2011
DOI: 10.1085/jgp.201110615
|View full text |Cite
|
Sign up to set email alerts
|

A TRPA1-dependent mechanism for the pungent sensation of weak acids

Abstract: Acetic acid produces an irritating sensation that can be attributed to activation of nociceptors within the trigeminal ganglion that innervate the nasal or oral cavities. These sensory neurons sense a diverse array of noxious agents in the environment, allowing animals to actively avoid tissue damage. Although receptor mechanisms have been identified for many noxious chemicals, the mechanisms by which animals detect weak acids, such as acetic acid, are less well understood. Weak acids are only partially dissoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
119
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(127 citation statements)
references
References 42 publications
7
119
0
1
Order By: Relevance
“…Weak acids from normal cellular metabolites, whereas not toxic under physiological conditions, can lead to intracellular acidification in a concentration and extracellular pH-dependent fashion (12,43,(57)(58)(59). In this study, we demonstrated that glycolic acid-induced intracellular acidification could lead to TRPV3 activation.…”
Section: Discussionmentioning
confidence: 53%
“…Weak acids from normal cellular metabolites, whereas not toxic under physiological conditions, can lead to intracellular acidification in a concentration and extracellular pH-dependent fashion (12,43,(57)(58)(59). In this study, we demonstrated that glycolic acid-induced intracellular acidification could lead to TRPV3 activation.…”
Section: Discussionmentioning
confidence: 53%
“…Similar results were found in recordings from a slice preparation of lingual epithelium, where focal application of sour stimuli elicited calcium responses in taste cells that correlated with the degree of intracellular acidification (20) To our knowledge, our experiments are the first to directly show that intracellular acidification alone, in the absence of extracellular acidification, increases cellular excitability in identified sour taste cells. For these experiments, we used two organic weak acids, acetic acid and propionic acid, which due to their small size and relatively high pK a values (4.76 and 4.88, respectively) can acidify the cell cytosol when used at neutral pH (27). Application of these acids at neutral pH caused a similar degree of intracellular acidification in both TRPM5 and PKD2L1 cells, but only PKD2L1 cells fired action potentials.…”
Section: Discussionmentioning
confidence: 99%
“…The inward K + current (at −80 mV) was unaffected by lowering the pH of the extracellular solution (to pH 6.0), but was strongly inhibited by 20 mM acetic acid, pH 6.0, a condition that acidifies the cell cytosol (27) (Fig. 2 A and B).…”
Section: Sour Taste Cells Respond To Intracellular Acidification Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the large family of transient receptor potential (TRP) ion-channels that includes the capsaicin (TRPV1) and menthol (TRPM8) receptors (Appendino et al, 2008;Inoue, 2005;Kim and Baraniuk, 2007;Woodard et al, 2007), the TRPA1 nociceptor has been implicated in the chemesthetic response to environmental irritants Macpherson et al, 2007b;McNamara et al, 2007) and even to CO 2 (Wang et al, 2010), as well as to weak organic acids (Wang et al, 2011). The TRPM5 channel has also been implicated in responses to irritants (Lin et al, 2008).…”
Section: ) Molecular Receptors For Trigeminal Chemesthesismentioning
confidence: 99%